2015
DOI: 10.1063/1.4915524
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport properties of halide solid solutions: Experiments vs equilibrium molecular dynamics

Abstract: The composition dependence of thermal transport properties of the (Na,K)Cl rocksalt solid solution is investigated through equilibrium molecular dynamics (EMD) simulations in the entire range of composition and the results are compared with experiments published in recent work [Gheribi et al., J. Chem. phys. 141, 104508 (2014)]. The thermal diffusivity of the (Na,K)Cl solid solution has been measured from 473 K to 823 K using the laser flash technique, and the thermal conductivity was deduced from critically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…Nonetheless, here we clearly claim that in such situations, EMD data should be considered as a reference, as the method has already proven its high predictive capability for several dynamic and transport properties for both simple and complex molten ionically bonded systems. 1822,25 Our calculated ionic conductivities are in good agreement with those of the two models. Both agree well with some data sets for both liquid and undercooled Al 2 O 3 : specifically, those reported by Shpil’rain et al 1 from melting temperature up to 3000 K, and those reported by Elyutin et al 4 below the melting temperature as low as 2050 K. Experimental data reported by Aleksandrov et al 2 and Arkel 6 are much higher than the other data sets and EMD calculations as well.…”
Section: Resultssupporting
confidence: 78%
“…Nonetheless, here we clearly claim that in such situations, EMD data should be considered as a reference, as the method has already proven its high predictive capability for several dynamic and transport properties for both simple and complex molten ionically bonded systems. 1822,25 Our calculated ionic conductivities are in good agreement with those of the two models. Both agree well with some data sets for both liquid and undercooled Al 2 O 3 : specifically, those reported by Shpil’rain et al 1 from melting temperature up to 3000 K, and those reported by Elyutin et al 4 below the melting temperature as low as 2050 K. Experimental data reported by Aleksandrov et al 2 and Arkel 6 are much higher than the other data sets and EMD calculations as well.…”
Section: Resultssupporting
confidence: 78%
“…for the prediction of the lattice thermal conductivity is illustrated in Figure 1 for CaF 2 (cubic,Fm 3m). This method is detailed extensively in our previous papers [8][9][10][11], here we provide only the main principles.…”
Section: Resultsmentioning
confidence: 99%
“…The most relevant formulation of Φ ph−ph was originally proposed by Callaway [17,18] and later by Slack [20,21] and relied only on a few key physical properties for its parametrization. Without going into details, which can be found in [8,10,12,19], Callaway and Salck's expression of Φ ph−ph , combined with Eq. 10, gives an expression which can be decomposed into two terms: a materials constants term (M at − Cst.)…”
Section: Modelling a Lattice Thermal Conductivity Modelmentioning
confidence: 99%
See 2 more Smart Citations